2004
DOI: 10.1002/art.20396
|View full text |Cite
|
Sign up to set email alerts
|

Knee adduction moment and development of chronic knee pain in elders

Abstract: Objective. To determine whether the adduction moment at the knee during locomotor activity contributes to the development of future chronic knee pain. Methods. We studied 132 community-dwelling elders who had undergone a full kinetic and kinematic motion analysis while performing 4 different activities: standing, walking, rising from a chair, and descending stairs. We contacted the participants 3-4 years after their baseline locomotion analysis and identified those who reported no knee pain at the time of moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
147
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(158 citation statements)
references
References 42 publications
7
147
0
4
Order By: Relevance
“…According to McGibbon et al (88,89) some individuals may "functionally adapt" by allowing one joint to compensate for the reduced power in the hip or knee joint. Others may "neuromuscularly adapt" by transferring a load away from the affected hip or knee joint or by inhibiting movement at that joint (83,90). Whether these adaptations should be permitted or eliminated, and how best to measure and address them, warrants further investigation (91).…”
Section: Biomechanical Considerations After Hip and Knee Arthroplastymentioning
confidence: 99%
“…According to McGibbon et al (88,89) some individuals may "functionally adapt" by allowing one joint to compensate for the reduced power in the hip or knee joint. Others may "neuromuscularly adapt" by transferring a load away from the affected hip or knee joint or by inhibiting movement at that joint (83,90). Whether these adaptations should be permitted or eliminated, and how best to measure and address them, warrants further investigation (91).…”
Section: Biomechanical Considerations After Hip and Knee Arthroplastymentioning
confidence: 99%
“…Knee joint loading, estimated using surrogate measures such as the external knee adduction moment (EKAM), has been implicated in both the development of knee pain and radiographic progression of medial knee OA in older adults (2,3). Knee load during walking is also positively associated with levels of subchondral bone change (4), worsening of bone marrow lesions (5), cartilage loss (6), and progression to total knee replacement in those with established disease (7).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have observed that during walking, higher peak KAM magnitudes are related to the development of knee pain [3] and with a 6.5-fold increase in risk of knee OA progression for every one percent increase in KAM (normalised by body weight x height) [4]. Accumulating cross-sectional evidence indicates an association between peak KAM and medial tibial cartilage degradation in people with knee OA [5,6].…”
Section: Introductionmentioning
confidence: 99%